Variability of Anticipatory Postural Adjustments During Gait Initiation in Individuals With Parkinson Disease. Issue 1 (January 2016) - Lin, Cheng-Chieh; Creath, Robert A.; Rogers, Mark W.
Abstract : Background and Purpose: In people with Parkinson disease (PD), difficulties with initiating stepping may be related to impairments of anticipatory postural adjustments (APAs). Increased variability in step length and step time has been observed in gait initiation in individuals with PD. In this study, we investigated whether the ability to generate consistent APAs during gait initiation is compromised in these individuals. Methods: Fifteen subjects with PD and 8 healthy control subjects were instructed to take rapid forward steps after a verbal cue. The changes in vertical force and ankle marker position were recorded via force platforms and a 3-dimensional motion capture system, respectively. Means, standard deviations, and coefficients of variation of both timing and magnitude of vertical force, as well as stepping variables, were calculated. Results: During the postural phase of gait initiation the interval was longer and the force modulation was smaller in subjects with PD. Both the variability of timing and force modulation were larger in subjects with PD. Individuals with PD also had a longer time to complete the first step, but no significant differences were found for the variability of step time, length, and speed between groups. Discussion and Conclusions: The increased variability of APAs during gait initiation in subjects with PD could affect posture-locomotion coupling, and lead to start hesitation, and even falls. Future studies are needed to investigate the effect of rehabilitation interventions on the variability of APAs during gait initiation in individuals with PD. Video abstract available for more insights from the authors (see Supplemental Digital Content 1, http://links.lww.com/JNPT/A119 ). Abstract : Supplemental Digital Content is Available in the Text.